2016
DOI: 10.1111/jdi.12469
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils in type 1 diabetes

Abstract: Type 1 diabetes is an autoimmune disease that afflicts millions of people worldwide. It occurs as the consequence of destruction of insulin‐producing pancreatic β‐cells triggered by genetic and environmental factors. The initiation and progression of the disease involves a complicated interaction between β‐cells and immune cells of both innate and adaptive systems. Immune cells, such as T cells, macrophages and dendritic cells, have been well documented to play crucial roles in type 1 diabetes pathogenesis. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 130 publications
3
78
0
1
Order By: Relevance
“…Another interesting finding in our work was excessive affinity of diabetic hMSCs to HUVECs obtained by SPR analysis. It was previously determined that the natural order of expression of adhesion molecules such as MAC‐1, selectins, and integrins was disturbed in cells exposed to hyperglycemic conditions [Huang et al, ]. Another reason for the reduction of angiogenic capacity in diabetic hMSCs was a decrease in differentiation potential into ECs and pericytes which coincided with a reduction in the rate of Dil‐Ac‐LDL uptake [Rezabakhsh et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting finding in our work was excessive affinity of diabetic hMSCs to HUVECs obtained by SPR analysis. It was previously determined that the natural order of expression of adhesion molecules such as MAC‐1, selectins, and integrins was disturbed in cells exposed to hyperglycemic conditions [Huang et al, ]. Another reason for the reduction of angiogenic capacity in diabetic hMSCs was a decrease in differentiation potential into ECs and pericytes which coincided with a reduction in the rate of Dil‐Ac‐LDL uptake [Rezabakhsh et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Different immune cells, such macrophages and dendritic and T cells, have been suggested to play crucial roles in type 1 diabetes pathogenesis [5355]. The contribution of autoreactive T cells to the destruction of pancreatic β cells as a consequence of an immunologically mediated destruction of the pancreatic tissues has been proposed as the key pathogenic mechanisms in type 1 diabetes [56, 57].…”
Section: Natural Killer Cells In Type 1 Diabetesmentioning
confidence: 99%
“…Clinical observations have indicated that circulating concentrations of zonulin and lipopolysaccharide (LPS), which can reflect the degree of gut permeability, are higher in diabetes patients than in healthy controls . Increased NET formation, along with neutropenia, may result primarily from a leaky gut, because the invasion of microorganisms can generate reactive oxygen species (ROS) and cause inflammation that can promote the abnormal activation of neutrophils . In addition, NET‐induced damage to intestinal epithelial and endothelial cells can aggravate gut leakage.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Increased NET formation, along with neutropenia, 6 may result primarily from a leaky gut, because the invasion of microorganisms can generate reactive oxygen species (ROS) and cause inflammation that can promote the abnormal activation of neutrophils. 13,14 In addition, NET-induced damage to intestinal epithelial and endothelial cells 15 can aggravate gut leakage. In a previous study, we proved that the staphylococcal nuclease that effectively degraded NETs relieved inflammation of the small intestine in non-obese diabetic (NOD) mice.…”
Section: Introductionmentioning
confidence: 99%